A comparative analysis of the film censorship and the film censorship board in Malaysia and Bangladesh - Islam, Md. Zahidul (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2017)
Since the 19th century film censorship has been being practiced by Malaysia and Bangladesh to protect society from any possible negative and immoral influences. In so doing, film censorship laws and guidelines were adopted by both countries. However, here exists some weaknesses in film censorship laws of both countries which are affecting the film industry to achieve a better position. Thus study adopts doctrinal and non-doctrinal methods of legal research to collect data. For the doctrinal method, the study uses a qualitative content analysis by analysing contents of library and online based literature, statutes, and case laws. For the non doctrinal method, the study uses semi-structured interview to collect data from the directors, actors, actresses and members of the film censorship board. It is found that film censorship laws are not the barrier to the freedom of speech and expression rather they are working as a mechanism to protect the entire society in various aspects. Moreover, the film censorship laws of both countries provide discretionary power to the Minister or the government which is a threat to the film industry. It is also found that film censorship laws of both countries did not mention any qualification for the member of the film censorship board. It is, therefore, suggested that there is a need for amendment of film censorship laws of both countries. The study concludes that if the reforms suggested herein are genuinely implemented, they will improve the film censorship laws of both countries.